ANALISIS PENERAPAN KARAKTER GOTONG ROYONG DENGAN MEDIA EDUCAPLAY FROGGY JUMPS DALAM PEMBELAJARAN PPKn DI SEKOLAH DASAR - Nisaul Husna, Fara; Martati, Badruli; Nanda Faradita, Meirza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of gotong royong character in students through the use of Educaplay Froggy Jumps media in Civics learning in elementary schools. This study used qualitative methods. Data collection techniques used were observation, interviews, and documentation. Data analysis used the Miles and Huberman technique. This study took place at SDN Mulyorejo 1 Surabaya, class 4A, with five groups of students as subjects. Research results based on observations, interviews, and documentation indicated that the use of Educaplay Froggy Jumps media can support the development of mutual cooperation (gotong royong) in students. This is evident in the emergence of mutual assistance in group discussions, cooperation in group work, and the responsibility of each group member for assigned tasks. Students also demonstrated active involvement and positive interactions throughout the learning process. Therefore, the use of Educaplay Froggy Jumps media in learning Civic can be an effective alternative learning medium for fostering and strengthening elementary school students’ mutual cooperation.